1964
DOI: 10.1002/jsfa.2740150108
|View full text |Cite
|
Sign up to set email alerts
|

A method of fractionation of flour proteins by means of gel filtration on Sephadex G‐100

Abstract: Flour and gluten extracts have been fractionated by gel filtration on Sephades G-loo, and starch gel electrophoresis has been used to investigate the degree of separation of the various protein components obtained. Although the method does not result in the isolation of individual proteins, it does separate them into certain groups, and offers possibilities for the study of protein interactions under various conditions in flours and doughs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1965
1965
1976
1976

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Gel Filtration Chromatography. Three major peaks and one minor peak were observed in the elution pattern of untreated gluten from Sephadex G-100 (Figure 3A) which is similar to those of Wright et al (1964) and Meredith and Wren (1966). The column was calibrated with standard proteins.…”
Section: Resultssupporting
confidence: 59%
“…Gel Filtration Chromatography. Three major peaks and one minor peak were observed in the elution pattern of untreated gluten from Sephadex G-100 (Figure 3A) which is similar to those of Wright et al (1964) and Meredith and Wren (1966). The column was calibrated with standard proteins.…”
Section: Resultssupporting
confidence: 59%
“…These results suggested that resolution of the watersoluble proteins on the basis of molecular size might be possible. Gel filtration studies reported (Jones et al, 1963;Wright et al, 1964;Godon et al, 1964) were concerned either with gluten or with the total acid extract of flour. The present investigation was undertaken to study the application of gel filtration using cross-linked dextrans for resolution or simplification of the protein mixture in the water-soluble fraction of flour.…”
Section: Fractionmentioning
confidence: 99%